Mass production of Diglyphus isaea (Hymenoptera: Eulophidae), a biological control agent of a Korean population of potato leaf miner Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae). Issue 2 (16th February 2017) - Maharjan, Rameswor; Kwon, Min; Kim, JuIl; Jung, Chuleui
Abstract: The potato leaf miner, Liriomyza huidobrensis (Blanchard), is an important pest of potato throughout the world, including Korea. A method was developed for mass rearing the parasitoid Diglyphus isaea (Walker) using faba bean, Vicia faba L. (Fabaceae), as the host‐plant and L. huidobrensis as the insect host. Faba bean plants were planted in pots and maintained in a greenhouse for about 15 d. Pots were then exposed to adult leaf miners in oviposition cages for 4 h. Plants containing late second to early third instar larvae were exposed to adult D. isaea in parasitoid cages for 24 h. The leaf area per pot after 15 d was 597.9 cm 2, which produced 103.33 larvae per pot. The number of adult parasitoids emerging per pot was 72.5; about 41% of these were female. The daily cost of parasitoid production was USD20.95 per 1000 individual parasitoids. The methodology developed for D. isaea could be used to rear other ectoparasitoids such as Hemiptarsenus spp. and Pnigalio sp. with different insect hosts like L. trifolii . This is why this mass‐rearing information is important for securing test insect materials for ecological and biological study of Liriomyza species, and also for developing a biological control for Liriomyza species other than L. huidobrensis by mass production of associated natural enemies. We are facing rapid agro‐ecosystem changes including pest systems. Continuous monitoring of Liriomyza in solanaceous crops is needed.